Nonlinear power dependence of the spectral properties of an optical parametric oscillator below threshold in the quantum regime - Shafiee, Golnoush; Strekalov, Dmitry; Otterpohl, Alexander; Sedlmeir, Florian; Schunk, Gerhard; Vogl, Ulrich; Schwefel, Harald G. L.; Leuchs, Gerd; Marquardt, Christoph (New Journal of Physics, 2020)
Photon pairs and heralded single photons, obtained from cavity-assisted parametric down conversion (PDC), play an important role in quantum communications and technology. This motivated a thorough study of the spectral and temporal properties of parametric light, both above the optical parametric oscillator (OPO) threshold, where the semiclassical approach is justified, and deeply below it, where the linear cavity approximation is applicable. The pursuit of a higher two-photon emission rate leads into an interesting intermediate regime, between above OPO threshold and very low pump power, where the OPO still operates considerably below the threshold but the nonlinear cavity phenomena cannot be neglected anymore. Here, we investigate this intermediate regime and show that the spectral and temporal properties of the photon pairs, as well as their emission rate, may significantly differ from the widely accepted linear model. The observed phenomena include frequency pulling and broadening in the temporal correlation for the down-converted optical fields. These factors need to be taken into account when devising practical applications of the high-rate cavity-assisted spontaneous PDC sources.
CRIS-Team WoS Importer:2020-08-21

Squeezed vacuum states from a whispering gallery mode resonator - Otterpohl, Alexander; Sedlmeir, Florian; Vogl, Ulrich; Dirmeier, Thomas; Shafiee, Golnoush; Schunk, Gerhard; Strekalov, Dmitry V.; Schwefel, Harald; Gehring, Tobias; Andersen, Ulrik Lund; Leuchs, Gerd; Marquardt, Christoph (Optica, 2019)
Squeezed vacuum states enable optical measurements below the quantum limit and hence are a valuable resource for applications in quantum metrology and also quantum communication. However, most available sources require high pump powers in the milliwatt range and large setups that hinder real-world applications. Furthermore, degenerate operation of such systems presents a challenge. Here, we use a compact crystalline whispering gallery mode resonator made of lithium niobate as a degenerate parametric oscillator. We demonstrate about 1.4 dB noise reduction below the shot-noise level for only 300 mu W of pump power in degenerate single-mode operation. Furthermore, we report a record pump threshold as low as 1.35 mu W. Our results show that the whispering gallery-based approach presents a promising platform for a compact and efficient source for nonclassical light. (c) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-12-06